Effects of cooking methods on the iron and zinc contents in cowpea (Vigna unguiculata) to combat nutritional deficiencies in Brazil - Pereira, Elenilda J. (Co-Action Publishing, 2014)
BACKGROUND: Because iron deficiency anemia is prevalent in developing countries, determining the levels of iron and zinc in beans, the second most consumed staple food in Brazil, is essential, especially for the low-income people who experience a deficiency of these minerals in their diet. OBJECTIVES: This study aimed to evaluate the effect of cooking methods by measuring the iron and zinc contents in cowpea cultivars before and after soaking to determine the retention of these minerals. METHODS: The samples were cooked in both regular pans and pressure cookers with and without previous soaking. Mineral analyses were carried out by Spectrometry of Inductively Coupled Plasma (ICP). RESULTS: The results showed high contents of iron and zinc in raw samples as well as in cooked ones, with the use of regular pan resulting in greater percentage of iron retention and the use of pressure cooker ensuring higher retention of zinc. CONCLUSIONS: The best retention of iron was found in the BRS Aracê cultivar prepared in a regular pan with previous soaking. This cultivar may be indicated for cultivation and human consumption. The best retention of zinc was found for the BRS Tumucumaque cultivar prepared in a pressure cooker without previous soaking.